2021
DOI: 10.1016/j.jmig.2021.06.011
|View full text |Cite
|
Sign up to set email alerts
|

Operative and Obstetric Outcomes after Single-port Laparoscopic Myomectomy: A Retrospective Single-center Analysis of 504 Cases

Abstract: To analyze the obstetric and operative outcomes of 504 cases of single-port laparoscopic myomectomy (SPLM). Design: Single-center retrospective study. Setting: A tertiary university hospital. Patients: A total of 502 patients (504 SPLM procedures) who underwent SPLM for symptom relief or growing myomas between October 2009 and April 2020. Interventions: Data on patient demographics, operative variables (estimated blood loss, hemoglobin decrease, operation time, perioperative complications, and postoperative ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…Several endoscopic techniques, including single‐site approach, have been proposed that could be potential minimally invasive substitute for open thyroidectomy 2,7,13,31 . With continuous understanding and mastery of single‐site approach technique, its application is increasingly extended in the field of minimally invasive surgery, such as in lung cancer surgery, colon cancer surgery, and gynecological surgery 32–40 . The anatomy of chest wall is different from that of abdominal cavity, which means less trocar intubations consequently lead to less collateral injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several endoscopic techniques, including single‐site approach, have been proposed that could be potential minimally invasive substitute for open thyroidectomy 2,7,13,31 . With continuous understanding and mastery of single‐site approach technique, its application is increasingly extended in the field of minimally invasive surgery, such as in lung cancer surgery, colon cancer surgery, and gynecological surgery 32–40 . The anatomy of chest wall is different from that of abdominal cavity, which means less trocar intubations consequently lead to less collateral injuries.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 7 , 13 , 31 With continuous understanding and mastery of single‐site approach technique, its application is increasingly extended in the field of minimally invasive surgery, such as in lung cancer surgery, colon cancer surgery, and gynecological surgery. 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 The anatomy of chest wall is different from that of abdominal cavity, which means less trocar intubations consequently lead to less collateral injuries. Therefore, the major advantage of trans‐areola single‐site approach is to minimize the surgical burden from multiple‐site approaches, in addition to invisible neck scars.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age of women across these studies ranged broadly from around 30 to 40 years, with most studies reporting a mean age in the early to mid-thirties, signifying a crucial overlap with both the peak reproductive years and the prevalent age range for myoma development (Table 2). For instance, Yu-cui Tian's study in 2014 [13] had an average age of 30.28 ± 3.99, while Yeon Hee Hong's 2021 study [22] reported a higher average age of 40.6 ± 6.6. This variation in age is crucial as it potentially impacts fertility outcomes post-myomectomy.…”
Section: Study Demographicsmentioning
confidence: 99%
“…Among these live births, 36 (92.3%) were term deliveries with an average gestational age of 38.2 ± 0.9 weeks, while the remaining 3 (7.7%) were premature deliveries, with an average gestational age of 34.0 ± 3.5 weeks. Cesarean section was the predominant mode of delivery, accounting for 36 infants (92.3%), although 3 infants (7.7%) were delivered vaginally [22].…”
Section: Splsm Vs Lsmmentioning
confidence: 99%
“…Compared to laparotomy, laparoscopic myomectomy has the benefits of less blood loss during the operation, shorter hospital stays, less scarring, and faster recovery [ 4 , 5 ]. Our group also has reported good surgical and fertility outcomes following single-port myomectomy [ 6 ]. However, no single surgical approach seems superior to others regarding the fertility rate, as available literature presents conflicting results [ 7 ].…”
Section: Introductionmentioning
confidence: 99%